Genetic evolution of parental populations and construction of core germplasm populations in qinghai spruce seed orchard based on SLAF-seq technology - Zhao, Hu; Xu, Erwen; Lv, Dong; Li, Wei; Zhao, Xingpeng; Jia, Xin; Yuan, Hao; Zhou, Rong (Frontiers in Genetics, 2025)
In order to explore the genetic background and genetic basis of the parental population of Qinghai spruce (Picea crassifolia Kom.) seed orchard, to reduce the cycle of genetic improvement of Qinghai spruce and the scale of germplasm resources, and to enhance the level of genetic improvement of Qinghai spruce. This study utilized the SLAF-seq technology to conduct genetic and evolutionary analysis on 165 germplasms from 11 provenances of Qinghai spruce seed orchards, and developed a total of 1964178 high-consistency single nucleotide polymorphism markers. Phylogenetic analysis classified them into three major groups, while population structure analysis revealed two subgroups. Through the Core Hunter II software, 33 (20%) core germplasms were selected, retaining all genetic diversity. This research provides a scientific basis for the genetic improvement of Qinghai spruce.